Balloon-augmented Onyx embolization of a dural arteriovenous fistula arising from the neuromeningeal trunk of the ascending pharyngeal artery: technical report. (8th December 2010) - Spiotta, Alejandro M; Hughes, Gwyneth; Masaryk, Thomas J; Hui, Ferdinand K
Abstract : Introduction: Intracranial dural arteriovenous fistulas (dAVFs) with perimedullary drainage are an uncommon but well-recognized lesion that can lead to spinal cord edema. The authors present a case of a foramen magnum dAVF with unilateral arterial supply from the ascending pharyngeal artery. Presentation: A 49-year-old male presented with a 1-year history of slowly progressive lower extremity weakness and underwent a two-level cervical corpectomy for presumed spondylotic myelopathy. On further workup, he was found to have a dAVF arising from the ascending pharyngeal artery. Intervention: Selective angiography revealed the origin of the neuromeningeal trunk, which was proximal to the arteriovenous fistula. The microcatheter was advanced into the neuromeningeal trunk past the origin of the inferior tympanic artery and origin of the hypoglossal artery. A 4×7 mm Hyperform balloon (EV3, Irvine, California, USA) was then delivered past the origin of the vessel supplying the skull base cranial nerves, but proximal to the microcatheter tip. The balloon was inflated and Onyx embolization was employed to obliterate the fistula with controlled penetration. The patient showed immediate postprocedural improvement in motor function. Discussion: Embolization of branches of the ascending pharyngeal artery carries risks of inadvertent embolization of branches of the neuromeningeal trunk as well as the risk for extracranial to intracranial anastamoses. An awareness of the highly variable anatomy of the ascending pharyngeal artery is necessary for the safe treatment of lesions supplied by this artery. This is, to the authors' knowledge, the first report of balloon-augmented embolization of an arteriovenous fistula arising from the neuromeningeal trunk.